THE SOCIAL EXCLUSION OF THE ELDERLY IN THE URBAN ENVIRONMENT - Fornasier, Mateus de Oliveira; Almeida Leite, Flavia Piva [UNESP] (Univ Estado Rio Janeiro, 2018)
The social exclusion of the elderly from the urban environment is studied - especially as regards the obliteration of their mobility rights and to participate in community life. It presents historical-philosophical and scientific factors about who the elderly are and how they are considered excluded from society. It also observer the exclusion of the elderly from the urban environment, with scientific data about exclusion factors in the world and in Brazil, also showing how the impairment in the urban mobility of the elderly is an increasing factor of their exclusion due to the biological aging. We conclude that urbanization must be understood as an event directly linked to globalization: not only space and urban interactions are achieved, but social relations in the countryside are also organized towards the urban center. In addition, functional systems presuppose the inclusion of all human beings, but in fact, exclude people who do not meet their requirements, and one type of exclusion serves as a foundation for others. Finally, it is not the search for an only responsible for exclusion, but rather the analysis that it is a complex of responsibilities, that is what should support public policies for inclusion of the elderly in the urban environment. Methodology: systemic-constructivist research method, with a qualitative approach and bibliographical research technique.
Keywords: Urban Environment; Exclusion; Elderly